KONTROVERSI REFORMASI USHUL FIQH DI KALANGAN PEMIKIR HUKUM ISLAM - Kholidah Kholidah (IAIN Padangsidimpuan, 2014)
The ide reform the ushul fiqh appearing along with the idea of reform to fiqh, because the ushul fiqh and fiqh are two things that cannot be separated. Ushul fiqh is the method that contains the procedure and the formation of low. in the other words ushul fiqh is the methology of Islamic law (minhaj istinbath al-ahkam), while fiqh that was excavated from the proposition through. however, the currency reform ushul fiqh among Islamic thinkers about the reform of ushul, namely stronghold that rejects reforms and stronghold that receives reform. a stronghold that rejects reforms argue that reform and development ushul fiqh not required, given that the ushul fiqh can accommodate and resolve that various problem that appear. that need to be done is to harness and maximize ushul fiqh as a methodology to produce fiqh more relevant to change. stronghold that receives reform argue the deconstruction of ushil fiqh is the inevitability of to release the fiqh of the allegation as a factor in the decline of Islam. because of the time and problems has changed and developing. a renewal of the ushul fiqh includes three things, namely: 1) that is orientation practical rather than abstract orientation, 2) developing the methodology of ushul fiqh to be relevant to reality and 3) extending componens ijtihad